Deixis Analysis of The Main Character in The Black Widow (2021) Movie (English Language and Literature (JELL), 2026)
The research aims to analyze the types, functions, and deictic usage of deixis used by the main character in the movie Black Widow (2021). This research employed Cruse’s (2000) theory to analyze the types of deixis, Cruse’s (2006) and Huang’s (2007) theories to analyze the functions of deixis, and Levinson’s (1983) theory to analyze the kinds of deictic usage. The data were collected from the script of the movie Black Widow (2021), which consists of utterances containing deixis used by the main character. The findings reveal five types of deixis used by the main character in the movie Black Widow (2021). Based on the data, person deixis was the most dominant type with 287 data, which shows its crucial role in personal references, followed by discourse deixis with 45 data, spatial deixis with 34 data, temporal deixis with 27 data, and social deixis with 16 data. These types of deixis function to clarify the roles participants, indicate place and time, express social relationships, and maintain discourse coherence. In addition, two kinds of deictic usage were identified, namely symbolic usage and gestural usage, with symbolic usage emerging as the most prevalent.
Keywords: Pragmatics, Deixis, Movie, Black Widow